Diagnostic criteria for sarcopenia and physical performance - Bijlsma, A. Y. (Springer Netherlands, 2013)
Relative and absolute muscle mass and muscle strength are used as diagnostic criteria for sarcopenia. We aimed to assess which diagnostic criteria are most associated with physical performance in 180 young (18–30 years) and 281 healthy old participants (69–81 years) of the European study MYOAGE. Diagnostic criteria included relative muscle mass (total or appendicular lean mass (ALM) as percentage of body mass), absolute muscle mass (ALM/height squared and total lean mass), knee extension torque, and handgrip strength. Physical performance comprised walking speed, Timed Up and Go test (TUG), and in a subgroup physical fitness. Diagnostic criteria for sarcopenia and physical performance were standardized, and the associations were analyzed using linear regression models stratified by age category, with adjustments for age, gender, and country. In old participants, relative muscle mass was associated with faster walking speed, faster TUG, and higher physical fitness (all p < 0.001). Absolute muscle mass was not associated with physical performance. Knee extension torque and handgrip strength were associated with faster walking speed (both p ≤ 0.003). Knee extension torque was associated with TUG (p = 0.001). Knee extension torque and handgrip strength were not associated with physical fitness. In young participants, there were no significant associations between diagnostic criteria for sarcopenia and physical performance, except for a positive association between relative muscle mass and physical fitness (p < 0.001). Relative muscle mass, defined as lean mass or ALM percentage, was most associated with physical performance. Absolute muscle mass including ALM/height squared was not associated with physical performance. This should be accounted for when defining sarcopenia.